Reduced Mitochondrial Membrane Potential Is a Late Adaptation of Trypanosoma brucei brucei to Isometamidium Preceded by Mutations in the γ Subunit of the F1Fo-ATPase. - Anthonius A Eze; Matthew K Gould; Jane C Munday; Daniel N A Tagoe; Valters Stelmanis; Achim Schnaufer; Harry P De Koning (PLoS Neglected Tropical Diseases)
Background Isometamidium is the main prophylactic drug used to prevent the infection of livestock with trypanosomes that cause Animal African Trypanosomiasis. As well as the animal infective trypanosome species, livestock can also harbor the closely related human infective subspecies T. b. gambiense and T. b. rhodesiense. Resistance to isometamidium is a growing concern, as is cross-resistance to the diamidine drugs diminazene and pentamidine. Methodology/principal findings Two isometamidium resistant Trypanosoma brucei clones were generated (ISMR1 and ISMR15), being 7270- and 16,000-fold resistant to isometamidium, respectively, which retained their ability to grow in vitro and establish an infection in mice. Considerable cross-resistance was shown to ethidium bromide and diminazene, with minor cross-resistance to pentamidine. The mitochondrial membrane potentials of both resistant cell lines were significantly reduced compared to the wild type. The net uptake rate of isometamidium was reduced 2-3-fold but isometamidium efflux was similar in wild-type and resistant lines. Fluorescence microscopy and PCR analysis revealed that ISMR1 and ISMR15 had completely lost their kinetoplast DNA (kDNA) and both lines carried a mutation in the nuclearly encoded γ subunit gene of F1 ATPase, truncating the protein by 22 amino acids. The mutation compensated for the loss of the kinetoplast in bloodstream forms, allowing near-normal growth, and conferred considerable resistance to isometamidium and ethidium as well as significant resistance to diminazene and pentamidine, when expressed in wild type trypanosomes. Subsequent exposure to either isometamidium or ethidium led to rapid loss of kDNA and a further increase in isometamidium resistance. Conclusions/significance Sub-lethal exposure to isometamidium gives rise to viable but highly resistant trypanosomes that, depending on sub-species, are infective to humans and cross-resistant to at least some diamidine drugs. The crucial mutation is in the F1 ATPase γ subunit, which allows loss of kDNA and results in a reduction of the mitochondrial membrane potential.